Pragmatic of advertising communication: relationship with literaty communicative processes - Catalá Pérez, Manuela (Tropelías: Review of Literary Theory and Comparative Literature, 1999)
Nowadays, a lot of advertising show ambiguity forms, with complicated means. It offers to one kind of public to these people decode this message correctly. This creative technical alludes to literary technichals. From the earliest time, advertising has used aesthetic elemenls like comunicalives indentures. From a pragmatical point of view, with the analysis of extralinguistic elements, it will be able to appreciate, with greatest precision, the resemblance between both models.